THE ROLE OF PARTICIPATION, INNOVATION CAPABILITY AND MEMBER'S TRUST IN COOPERATIVE PERFORMANCE, WITH MEDIATION OF COOPERATIVE MEMBERS' COMMITMENTS (STUDY ON COOPERATIVE BOARDING BOARDS IN MATARAM CITY IN 2020) - Marlina, Marlina (Dinasti International Journal of Management Science, 2022)
This study aims to determine the effect of the role of member participation, ability to innovate, and member trust on cooperative performance mediated by member commitment. The study was conducted at three cooperative boarding schools in the city of Mataram. The method used in this research is a survey method with path analysis. The population in this study were 257 members of the cooperative with a sample of 157 people. Sampling was carried out using the slovin formula. The research instrument is in the form of closed questions on all research variables with 5 alternative answers following the linkert scale. Based on the results of the study, it was concluded that there was an influence of the ability to innovate, and the trust of members on the performance of the cooperative, either directly or mediated by the commitment of members with a value of Sig < 0.05 . Meanwhile, member participation has no effect on cooperative performance, either directly or mediated by member commitment.